2007
DOI: 10.1002/cmdc.200700155
|View full text |Cite
|
Sign up to set email alerts
|

Octa‐O‐bis‐(R,R)‐Tartarate Ditellurane (SAS)—a Novel Bioactive Organotellurium(IV) Compound: Synthesis, Characterization, and Protease Inhibitory Activity

Abstract: Octa-O-bis-(R,R)-Tartarate Ditellurane (SAS) is a new Te(IV) compound, comprised of two tellurium atoms, each liganded by four oxygen atoms from two carboxylates and two alkoxides of two tartaric acids. Unlike many other Te(IV) compounds, SAS was highly stable in aqueous solution. It interacted with thiols to form an unstable Te(SR)(4) product. The product of the interaction of SAS with cysteine was isolated and characterized by mass spectroscopy and elemental analysis. SAS selectively inactivated cysteine pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Te-SG [33,34]. The difference in Cathepsin inhibition values exhibited by the same compound arise owing to specific features of the various sub-sites in the enzyme which are responsible for the specificity of the protease [35,36].…”
Section: Decane (1) (3e)-2-chloro-3-(chloromethylidene)-2-(4-methoxymentioning
confidence: 99%
“…Te-SG [33,34]. The difference in Cathepsin inhibition values exhibited by the same compound arise owing to specific features of the various sub-sites in the enzyme which are responsible for the specificity of the protease [35,36].…”
Section: Decane (1) (3e)-2-chloro-3-(chloromethylidene)-2-(4-methoxymentioning
confidence: 99%
“…In particular, the irreversible inhibition activity of AS101 was described and, subsequently, an extensive study of other biological properties of this compound ensued. [8][9][10][11] As cathepsin B is involved in a number of human diseases, [12][13][14] the development of selective inhibitors of cathepsin B has become a mainstay in the search of chemotherapeutic agents. 15 Recently, Cunha et al 16,17 presented a series of eight organotellurium(IV) compounds which exhibited more effective inhibition of Cathepsin B compared with AS101.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we demonstrated that AS101 and SAS specifically inactivate cysteine proteases, while exhibiting no effect on the other families of serine-, aspartic-and metalloproteases, in good agreement with predictions based on their unique Te IV -thiol chemistry. Furthermore, the proteolytic activity of the inactivated cysteine proteases could be recovered by reducing agents such as NaBH 4 , further supporting the suggestion that the inactivation process involves oxidation of the catalytic thiol to a disulfide [8,9].…”
Section: Biological Activity Of Tellurium Compoundsmentioning
confidence: 67%
“…The compounds exerting the most pronounced biological activities are Te IV valences, including AS101 [ammonium trichloro (dioxoethylene-O,O_)tellurate] [7,8], and SAS [octa-O-bis-(R,R)-tartarate ditellurane] [8,9]. Our studies have pioneered a new area, demonstrating the potency of inorganic Te IV compounds in biology.…”
Section: Biological Activity Of Tellurium Compoundsmentioning
confidence: 93%